Optimization of Quality Attributes and Atomic Force Microscopy Imaging of Reconstituted Nanodroplets in Baicalin Loaded Self-Nanoemulsifying Formulations - Géza Jakab; Viktor Fülöp; Tamás Bozó; Emese Balogh; Miklós Kellermayer; István Antal (MDPI AG, 2018)
The objective of the study was to develop baicalin loaded liquid self-nanoemulsifying drug delivery systems (BSNEDDS) and to characterize them by physicochemical methods in order to optimize the composition and quality attributes. Atomic force microscopy (AFM) was utilized to evaluate the morphological characteristics and size distribution of reconstituted nanoemulsion droplets with a new sample preparation method for the elucidation of individual nanodroplets without any signs of coalescence. Response surface methodology and desirability approach was used to select the optimized composition related to droplet size, zeta-potential, polydispersity index (PDI), and turbidity characteristics. Droplet size distribution measured by dynamic light scattering method was highly desirable with 52.87 ± 0.5322 nm, which was confirmed by AFM imaging. The optimized formula contains Peceol® (14.29%, w/w), Kolliphor® EL (57.14%, w/w), and Transcutol® P (28.57%, w/w). Long-term stability analysis did not show any significant change in droplet size or PDI over the investigated period. More than 40.5-times solubility improvement was achieved with the optimized BSNEDDS correlated to solubility of baicalin in distilled water. In vitro dissolution studies at pH 1.2 and pH 6.8 were performed and revealed that the optimized BSNEDDS formula showed pH independent drug dissolution, and 100% of incorporated baicalin dissolved within five minutes in rapidly dispersing nanodroplets.